Internal Factors, External Factors and Earnings Management: Moderating Effects of Auditor Industry Specialization - Agung Prayogi; Puji Lestari; Christina Tri Setyorini (Global Financial Accounting Journal, 2022)
Purpose - Earnings management is one of the agency problems in a company. Furthermore, it illustrates the opportunistic behavior of company managers and can be a bad signal for company stakeholders. This research was conducted with the aim of testing the auditor industry specialization as a moderator in the effect of financial distress, tax planning, ownership structure, and audit quality on earnings management. Research Method - This research uses 288 data from 36 manufacturing companies listed on the Indonesia Stock Exchange from 2012 to 2019, using a purposive sampling method. The model used in this research was analyzed using multiple linear regression and moderation test (sub-group analysis and ANOVA test). Findings - According to the findings, managerial ownership and audit quality have a negative effect on earnings management. On the other hand, financial distress, tax planning, and institutional ownership are not significant to earnings management. Meanwhile, by taking into account firm size, profitability, and leverage, auditor industry specialization can be found to moderate the relationship between financial distress, tax planning, managerial ownership, and institutional ownership with earnings management. However, specialization in the audit industry has no effect on the on the effect of audit quality on earnings management. Implication - The presence of managerial ownership and external auditors can serve as a de-confliction mechanism. Companies can consider giving managers the opportunity to own company shares and use the Big Four KAP auditors in order to create better oversight. In addition, companies can consider using auditors from KAPs who have a lot of experience in certain industries.